Prognostic value of perineural invasion in gastric cancer: a systematic review and meta-analysis. - Jing Deng; Qihan You; Yang Gao; Qing Yu; Peng Zhao; Yulong Zheng; Weijia Fang; Nong Xu; Lisong Teng (PLoS ONE)
Background The prognostic role of perineural invasion in gastric cancer is controversial. Here, we present a systemic review and meta-analysis of the association between perineural invasion and survival in resectable gastric cancer patients. Methods A comprehensive literature search for relevant reports published up to April 2013 was performed using PubMed, Embase, Web of Science and Wanfang Data. Studies that investigated the role of perineural invasion with a sample size greater than 100 were included and analyzed. Results A total of 30,590 gastric cancer patients who had undergone curative gastrectomy from twenty-four studies were included. The median rate of perineural invasion positive was 40.9% (6.8%-75.6%). Fourteen studies investigated overall survival unadjusted for other variables in 23,233 gastric cancer patients. The relative hazard estimates ranged from 0.568-7.901 with a combined random effects estimate of 2.261 (95% CI = 1.841-2.777, P = 0.000). The effect of perineural invasion on overall survival adjusted for other prognostic factors was reported in 17 studies incorporating 8,551 cases. The hazard estimates ranged from 0.420-8.110 with a pooled random effects estimates of 1.484 (95% CI = 1.237-1.781, P = 0.000). There was heterogeneity between the studies (Q = 49.22, I-squared = 67.5%, P = 0.000). Disease-free survival was investigated adjusted in four studies incorporating 9,083 cases and the pooled fixed hazard ratio estimate was 1.371(95% CI = 1.230-1.527, P = 0.000). Conclusion Perineural invasion is an independent prognostic factor affecting overall survival and disease-free survival of gastric cancer patients who had undergone the curative resection. This effect is independent of lymph node status, tumor size and the depth of invasion as well as a range of other biological variables on multivariate analysis. Large prospective studies are now needed to establish perineural invasion as an independent prognostic marker for gastric cancer.